2004
DOI: 10.1175/jpo2632.1
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Ice Drift on the Northeastern Shelf of Sakhalin Island

Abstract: Ice-drift velocity records from coastal radar stations, combined with data from moored current meters and coastal wind stations, are used to examine sea-ice motion off the northeastern coast of Sakhalin Island in the Sea of Okhotsk. Ice motion is shown to be governed primarily by diurnal tidal currents and wind-induced drift, which explain 92%–95% of the total ice-drift variance. Diurnal tidal motions predominate off the northern Sakhalin coast, accounting for 65%–80% of the variance, while low-frequency wind-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Mizuta et al (2005) showed that CTWs are induced by alongshore wind stress in the Sakhalin coast even in the sea ice season. Under the realistic depth profile and stratification off the Sakhalin coast, located in relatively high latitudes (468-558N), the CTWs have nearly barotropic structure (Shevchenko et al 2004;Mizuta et al 2005;Ono et al 2006). In addition, from the dispersion relations, the waves with the period of ;10 days can be treated as long waves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mizuta et al (2005) showed that CTWs are induced by alongshore wind stress in the Sakhalin coast even in the sea ice season. Under the realistic depth profile and stratification off the Sakhalin coast, located in relatively high latitudes (468-558N), the CTWs have nearly barotropic structure (Shevchenko et al 2004;Mizuta et al 2005;Ono et al 2006). In addition, from the dispersion relations, the waves with the period of ;10 days can be treated as long waves.…”
mentioning
confidence: 99%
“…The spectral density of the wind decreases monotonically without any specific peak (not shown). We arbitrarily choose 0.1 cpd as a representative of low frequency and its wind speed is set to jÛ a j 5 7 m s prominent off the Sakhalin coast (Shevchenko et al 2004). The spatial distribution of g for the case of 0.1 cpd is shown in Fig.…”
mentioning
confidence: 99%
“…Eulerian data have also been analysed (e.g., Schevchenko et al, 2004) In the observations, Eulerian spectrum is at higher level than the Lagrangian spectrum as anticipated. The difference does not show significant variations across the spectrum, but the slopes of the spectra show indication to differ at high frequencies.…”
Section: Lagrangian and Eulerian Spectramentioning
confidence: 97%
“…Many observation programmes have been performed on sea ice kinematics, and, consequently a number of papers have been published on ice velocity time series analyses (e.g., Hibler et al, 1974;Ono, 1978;McPhee, 1980;Thorndike and Colony, 1980;Leppäranta, 1981;Hutchings and Hibler, 2002;Schevchenko et al, 2004;Geiger and Perovich, 2008). Here ice motion data from two different kinds of basins are used to extend the empirical knowledge toward higher frequencies and to compare the observed spectra of ideal models.…”
Section: Data Collectedmentioning
confidence: 99%
See 1 more Smart Citation